ACCELERATION OF ABILITY TO WRITE FREE POETRY IN CLASS V STUDENTS OF AN-NISA INTEGRATED ISLAMIC ELEMENTARY SCHOOL, DELI SERDANG REGENCY - Dewi Sartika Panggabean; Zulvia Misykah; Putri Sari Ulfa Sembiring; Asmidar Dalimunte; Arnisa Rambe (Sean Institute, 2023)
This study aims to describe the ability to write free poetry in class V students of Islam Terpadu An-Nisa School, Deli Serdang Regency, in terms of the inner structure and physical structure of poetry. The population in this study were all 92 class V students of Islam Terpadu An-Nisa School, Deli Serdang Regency, which were divided into 3 classes. The sample was determined as many as 40 students of Islam Terpadu An-Nisa School, Deli Serdang Regency. The type of sampling used is cluster random sampling. This research is a descriptive study of facto exposure with research subjects namely students of class V-1, V-2, V-3, totaling 92 people, carried out in odd semesters, using data collection techniques in the form of performance tests (poetry writing), while techniques data analysis used is descriptive statistics. The results of the study showed that class V students at Islam Terpadu An-Nisa School, Deli Serdang Regency, were categorized as incapacitated or inadequate.